Options For Utilising Surplus Energy Generated by Renewable Sources - Andrzej JAMROZ; Robert LISOWSKI (Communications of International Proceedings, 2022)
At the current stage of the development of civilisation, new problems related to the variety of energy sources come up. Currently, most of the world’s final energy demand is covered by the energy generated by burning fossil fuels. This causes a significant deterioration of the natural environment and heavily contributes to the greenhouse effect. When we talk about energy demand, we mean not only electricity but also heat and fuel for powering vehicles. As a result of the above issues, there is an increasing interest in hydrogen as an alternative source of energy to fossil fuels. Its use will contribute to the improvement of the environment due to the fact that the product of its combustion is pure water. Currently, much research is being carried out on the production, storing and processing of this element all over the world. The undeniable fact is that hydrogen is a component of water, and we have an abundance of it on our planet. Green hydrogen can be produced through the process of electrolysis. In this paper, we will discuss the different methods of producing, storing and transporting this gas.
Keywords: Source of Renewable Electric Energy; Photovoltaic; Hydrogen